The degree of availability of some multiple intelligences ( Linguistic, Mathematical, Kinetic ) in the Book " Arabic is my language " for the basic third (Journal of Hama University, 2026)
The study aimed to reveal the degree of availability of some multiple intelligences ( Linguistic, Mathematical, Kinetic )in the Book " Arabic I my language " for the basic third Grade, The researcher developed a content analysis questionnair that included three levels of intelligence: linguistic, logical and kinesthetic intelligence, After testing the validity and reliability of the study tool, the researcher analyzed the content of two volumes of the Arabic is mg language textbook of the basic third, and the results of the search for: the book did not neglect any of the intelligences but achieved different percentages. The highest type of intelligence was ( linguistic intelligence ) by ( %64 ), with a moderate degree, by ( %20.74 ), with a low degree, ( logical intelligence ) and ( kines thetic intelligence ) at the last Trak by ( %15.26 ), with too low degree, in the light of the results of the research, the researcher recommended to take care of the indicators of neglected intelligence and to include in the content of the book with the need to take into account the  multiple intelligences of students and diversi Fication in the construction of Arabic language curricula, and suggested to Promoting a more comprehensive integration multiple intelligences into the curricula of the first stage of basic education through the inclusion of diverse, applicable activities
Keywords: Multiple intelligences, The book of